Multifaceted Assessment of Health Literacy in People Receiving Dialysis: Associations With Psychological Stress and Quality of Life. (1st August 2016) - Dodson, Sarity; Osicka, Tanya; Huang, Louis; McMahon, Lawrence P.; Roberts, Matthew A.
Abstract : Health literacy (HL) refers to a person's ability to engage effectively with health information and services. We aimed to describe the HL of people receiving dialysis and the factors associated with it. A cross-sectional design was used, with demographic and clinical data as predictors. Participants were people receiving dialysis at a metropolitan health service in Melbourne, Australia. Health consumers with conditions not requiring dialysis were included for comparison. The Health Literacy Questionnaire, Kidney Disease Quality of Life–36, and Depression Anxiety Stress Scales–21 were administered. Participants ( M age = 68.2 ± 13.7 years; n = 57 males) were 76 people receiving hemodialysis within a dialysis unit, 16 people receiving home peritoneal dialysis, and 8 people receiving home hemodialysis. Participants scored higher on the HL domains social support for health and engagement with health care providers but lower on active management of health than the comparison group ( n = 813). Hierarchical cluster analysis revealed 2 clusters within the dialysis sample representing higher ( n = 43) and lower ( n = 57) profiles of HL. The higher HL cluster reported better quality of life across 4 of 5 domains of the Kidney Disease Quality of Life–36, fewer symptoms of depression and anxiety, and higher serum albumin (mean difference = 2.06 g/L, p = .04) than the lower HL cluster. These results show that people receiving dialysis feel better supported and informed about their health than other health consumers but are less active in managing it. Higher HL is associated with better mental health and quality of life. Identifying HL characteristics may help direct specific interventions to improve patient education and support.